Consumer Behavior and Decision-Making in Health Insurance Policy Purchases in Nepal - Prasad Joshi, Surendra; Kumar Dahal, Rewan; Karki, Dipendra; Ghimire, Binod (Nepalese Journal of Insurance and Social Security, 2024)
Purpose: Health insurance serves as a lifeline with the prospect of financial security in the face of an insurance system, thinking that accidents in human life can occur at any time. This study analyzes the elements that influence people’s decisions to obtain health insurance coverage in Nepal. Design/methodology/approach: It used descriptive and causal research design based on primary data collected from 385 prospective insurance consumers. It employed correlation and multiple regression analysis to conclude. Findings: Findings show that there was a significant relationship between mental accounting, pricing, premium, brand trust, and risk perception with individuals’ insurance purchase decisions. Brand trust was revealed as the most powerful predictor, followed by mental accounting. Conclusion: The study concluded that financial concerns are important; trust in the insurance companies and consumers’ mental accounting of health-related expenses have a greater influence on purchasing behavior. Implications: This study emphasizes the importance of brand trust and mental accounting in health insurance decisions in Nepal. The findings support efforts to improve financial security and achieve universal health coverage. JEL Classification: D14, G22, I13, D91